Impact of Renin-Angiotensin System Inhibitors on Disease Characteristics in Patients with Localized Prostate Cancer Treated with Radical Prostatectomy: A European Association of Urology Young Academic Urologists Prostate Cancer Working Group Multi-institutional Study - Nastasiia Artamonova; Mona Kafka; Laura Faiss; David Avetisyan; Ignacio Puche Sanz; Giulia La Bombarda; Gennaio Iacono; Fabio Zattoni; Eberhard Steiner; Caroline D’Elia; Armin Pycha; Michael Ladurner; et al. (European Urology Open Science)
Background and objective: Collagen biosynthesis is intricately involved in the development and progression of solid tumors. Renin-angiotensin system inhibitors (RASi) impede TGF-β-mediated collagen synthesis in tumors by hindering activation of the angiotensin receptor. Our aim was to investigate a potential association between RASi use and the aggressiveness of prostate cancer (PCa). Methods: We conducted a retrospective multicenter analysis for a cohort of 1250 patients with PCa who underwent radical prostatectomy (RP) between 1990 and 2023 in four European high-volume centers. The study cohort comprised 625 RASi-treated patients and 625 age-matched RASi-naïve patients. Data for various parameters were collected, including age at RP, body mass index (BMI), prostate volume, prostate-specific antigen (PSA), percentage of free PSA, Gleason score (GS) at biopsy and RP, TNM stage, and the rate of biochemical recurrence (BCR). Clinical parameters for patients with and without RASi treatment were documented. Differences between the groups were compared using a Mann-Whitney U test and χ2 tests. Survival analyses were performed using the Kaplan-Meier method. Key findings and limitations: As expected, the RASi group had higher BMI levels than the RASi-naïve group (p < 0.001). However, RASi use was not associated with key markers of PCa aggressiveness such as GS upgrading from biopsy to RP (p = 0.089), surgical margin status (p = 0.109), and lymph node involvement (p = 0.33). Moreover, there were no significant differences between the groups in BCR incidence (p = 0.258) or the time to BCR (p = 0.683). Conclusions and clinical implications: Our findings indicate that RASi therapy does not have a significant effect on the biological aggressiveness of PCa. Patient summary: We analyzed data for 1250 patients with prostate cancer and found that the use of a commonly prescribed high blood pressure medication was not associated with a less aggressive form of localized prostate cancer.